2021
DOI: 10.7759/cureus.17313
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Google Trends to Track Online Interest in Elective Hand Surgery During the COVID-19 Pandemic

Abstract: IntroductionElective hand surgery encompasses a large volume of orthopaedic cases annually. Carpal tunnel syndrome, ganglion cysts, and trigger digits are some of the most common pathologies treated by hand surgeons. In the midst of the COVID-19 pandemic, patient's interest in elective hand surgery for these conditions is uncertain. The objective of this study is to use Google Trends to track online interest in elective hand surgery in the United States during the COVID-19 pandemic. MethodsOnline search trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…This suggests that while elective surgery RSV is primarily used as an indicator of interest, it could also be used to gauge demand, idempotent to the presence of acute, disruptive events. The findings that the drop in demand for elective surgeries after the COVID-19 peak on March 14, 2020, caused significant decreases in search volume [5,17] is supported in this study as we found that the COVID-19 peak increased COVID-19 RSV and decreased elective surgery RSV and surgical volume. By finding the algebraic relationship between RSV and caseloads, models can be generated to accurately predict surgical volume as RSV is provided daily by Google Trends.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…This suggests that while elective surgery RSV is primarily used as an indicator of interest, it could also be used to gauge demand, idempotent to the presence of acute, disruptive events. The findings that the drop in demand for elective surgeries after the COVID-19 peak on March 14, 2020, caused significant decreases in search volume [5,17] is supported in this study as we found that the COVID-19 peak increased COVID-19 RSV and decreased elective surgery RSV and surgical volume. By finding the algebraic relationship between RSV and caseloads, models can be generated to accurately predict surgical volume as RSV is provided daily by Google Trends.…”
Section: Discussionsupporting
confidence: 79%
“…This provides a measure from 0 to 100 in the relative search interest for a given search term over a specific time period. Each term was searched individually as was done in previous work with Google Trends since searching multiple terms at once would instead provide a relative value between the searches [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is mirrored by our study’s findings, where we also found decreased online interest in cervical cancer and the Pap test after the pandemic was declared. Expectedly, as interest in COVID-19 increased ( Effenberger et al, 2020 ), online interest in other health topics decreased transiently ( Alonto et al, 2022 , Dzaye et al, 2021 , Jella et al, 2020 , Mohty et al, 2021 ). On the other hand, increased online interest in the HPV vaccine may be related to the general increased online interest in vaccines given the pandemic – global online interest in both pneumococcal and influenza vaccines also peaked in February and March 2020 ( Paguio et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%